Academic writing : intercultural and textual issues - Ventola, Eija.; Mauranen, Anna. (Amsterdam ; Philadelphia : John Benjamins Pub., 1996)
Writing is crucial to the academic world. It is the main mode of communication among scientists and scholars and also a means for students for obtaining their degrees. The papers in this volume highlight the intercultural, generic and textual complexities of academic writing. Comparisons are made between various traditions of academic writing in different cultures and contexts and the studies combine linguistic analyses with analyses of the social settings in which academic writing takes place and is acquired. The common denominator for the papers is writing in English and attention is given t.
ACADEMIC WRITING INTERCULTURAL AND TEXTUAL ISSUES; Editorial page; Title page; Copyright page; Table of contents; Preface; Acknowledgements; I. CONTEXT AND GENRE; Strategic Vagueness in Academic Writing; Three Hypothetical Strategies in Philosophical Writing; Occluded Genres in the Academy: The Case of the Submission Letter; Academic Writing in Computer Science: A Comparison of Genres; The Hidden Curriculum of Technology for Academic Writing Toward a Research Agenda; II. CULTURE AND TEXTUALITY.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Colección Educación intercultural; English language -- Rhetoric -- Study and teaching; Academic writing -- Study and teaching; Academic writing -- Social aspects; Intercultural communication; Multicultural education; Language and culture; Écriture savante -- Étude et enseignement; Écriture savante -- Aspect social; Éducation interculturelle; Langage et culture; Communication interculturelle; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; Academic writing -- Social aspects; Academic writing -- Study and teaching; English language -- Rhetoric -- Study and teaching; Intercultural communication; Language and culture; Multicultural education; Schrijftaal; Academici; Anglais (langue) -- Rhétorique.; Multiculturalisme; Rhétorique.; Langage et culture